Peran Pemangku Kepentingan dalam Rehabilitasi Orang dengan Disabilitas Psikososial (ODDP) di Kalurahan Sidoagung dalam Perspektif Peran dan Pemberdayaan Komunitas - Dinda Pramesti; Erni Saharuddin (PUBLICNESS: Journal of Public Administration Studies, 2025)
This study aims to identify and analyze the roles of stakeholders in the rehabilitation process of People with Psychosocial Disabilities (ODDP) in Sidoagung Village. A descriptive qualitative approach was applied, with primary data collected through interviews, observations, and direct documentation from key informants, as well as secondary data from documents, literature, regulations, and previous research. The results revealed that key stakeholders include local governments, health workers, social organizations, families, and communities. Each plays a specific role, ranging from providing health services and social assistance to economic empowerment. Collaboration between stakeholders has been shown to increase the effectiveness of rehabilitation, accelerate social reintegration, and reduce stigma against ODDP. However, challenges such as limited resources and limited public understanding still hamper the process. This study recommends strengthening collaboration between stakeholders and community education programs to build an inclusive environment that supports sustainable rehabilitation.